Single nucleotide polymorphism-based visual identification of Rhodiola crenulata using the loop-mediated isothermal amplification technique - Hao, Li; Shi, Xin; Wen, Shiyu; Yang, Caiye; Chen, Yaqi; Yue, Samo; Chen, Jiaqiang; Luo, Kexin; Liu, Bingliang; Sun, Yanxia; Zhang, Yi (Frontiers in Plant Science, 2025)
IntroductionRhodiola crenulata (Hook.f. & Thomson) H.Ohba, a member of the Crassulaceae family, is a traditional Chinese medicine recognized as the original source of Rhodiolae Crenulatae Radix et Rhizoma in the 2020 edition of the China Pharmacopoeia. It has been widely used in both Asia and Europe to enhance stress resistance and reduce fatigue. However, the classification of Rhodiola species can lead to confusion, raising safety concerns in the herbal medicine market.MethodsThe cleaved amplified polymorphic sequence (CAPS) RT-PCR was used to identify the single nucleotide polymorphism (SNP) sites, based on which the loop-mediated isothermal amplification (LAMP) was employed to develop the method in Rh. crenulata identification. The specific loop backward primers, reaction temperature, reaction time, and color indicators were screened and optimized.ResultsSingle nucleotide polymorphism (SNP) sites were identified between Rh. crenulata and two closely related species. Based on the identified SNP sites, the optimal real-time fluorescence LAMP system to identify Rh. crenulata was constructed with the most efficient specific loop backward primers, reaction temperature. The final detection system exhibited a sensitivity of up to 1,000 copies of the target DNA, maintaining a constant reaction temperature of 62°C within 35 minutes. To facilitate visualization, we incorporated two color indicators, hydroxy naphthol blue (HNB) and neutral red (N-red), into the reaction system.DiscussionCollectively, we developed a simple, rapid, specific, sensitive, and visible method to distinguish Rh. crenulata from other two Rhodiola species and Rh. crenulata hybrids. This approach has significant potential for applications in pharmaceutical industry.